Technology and legal profession - Ali Mohamed, Ashgar Ali; Venugopal, A Vijayalakshmi; Daud, Mahyuddin; Ahmad, Muhamad Hassan; Amirnuddin, Puteri Sofia (CLJ Malaysia Sdn. Bhd., 2025)
With the implementation of technology in the delivery of justice and the expansion of the courtroom beyond the physical four walls, members of the legal profession must prepare themselves and learn to adopt technology. There is no alternative. “Adapt or be dropped”.1 Previously, one could experience great success in the profession if he worked hard, understanding the law, and advocating efficiently for clients. However, future law practice will require skills far beyond the knowledge of the law. In fact, senior lawyers who have been in practice for many years are now beginning to realise that the “old way” is no longer sufficient. Having said the above, this Chapter discusses technology in the delivery of justice system and how members of the legal profession to adapt and embrace changes to keep pace with a rapidly evolving world.